mt1_sample_solution

mt1_sample_solution - Sample Exam 1 Solutions Antoine...

Info iconThis preview shows pages 1–5. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Sample Exam 1 Solutions Antoine Calvez, Eric Angle Physics Department, University of California Los Angeles. * (Dated: October 17, 2006) * Electronic address: acalvez@ucla.edu,angle@physics.ucla.edu 1 I. SAMPLE EXAM PROBLEM 1. 1. Hookes Law is F x =- kx . Newtons Second Law is F x = m d 2 x dt 2 . [1] 2. Setting these expressions equal to one another gives F x =- kx = m d 2 x dt 2 m d 2 x dt 2 + kx = d 2 x dt 2 + k m x = 0, or d 2 x dt 2 + 2 x = 0 , where 2 = k m . 3. x ( t ) =- A cos ( t ) v ( t ) = d dt x ( t ) = A sin ( t ) v ( t ) = A sin ( t ) a ( t ) = d dt v ( t ) = A 2 cos ( t ) a ( t ) = A 2 cos ( t ) . 4. Plots of x , v , and a are shown below: 2 3 5. We aim to show that if x =- A cos ( t ), d 2 x dt 2 + 2 x = 0 is satisfied. Plug- ging this expression for x into the left hand side of the differential equation gives d 2 dt 2 [- A cos ( t )] + 2 [- A cos ( t )] A 2 cos ( t )- A 2 cos ( t ) = 0. X 6. = q k m [ ] = q [ k ] m = q [ F ] mL = q m [ a ] mL = q L LT 2 = q 1 T 2 = 1 T [ ] = 1 T . Angular frequency, , should have units of 1 T , since this is the same dimension of frequency f , and we know and f have the same dimension from the expression = 2 f . 7. f = 1 T = 2 . T , the period, is the time one complete oscillation takes. f , the frequency, is the number of complete oscillations that occur per second. , the angular frequency, is the number of radians traversed per second by the argument of the sinusoidal function used in the position function of the oscillator. 8. f = 2 f = 1 2 r k m . T = 1 f T = 2 r m k . 9. T = 2 p m k T = 2 q 4 m k = 4 p m k = 2 T T increases by a factor of 2. f = 1 2 q k m f = 1 2 q k 4 m = 1 4 q k m = 1 2 f f decreases by a factor of 2. = q k m = q k 4 m = 1 2 q k m = 1 2 decreases by a factor of 2. 10. T = 2 p m k T = 2 p m 4 k = p m k = 1 2 T T decreases by a factor of 2. f = 1 2 q 4 k m f = 1 2 q 4 k m = 1 q k m = 2 f f increases by a factor of 2. = q k m = q 4 k m = 2 q k m = 2 increases by a factor of 2. 11. None of the physical quantities T , f , or depend on A , so if the amplitude changes, none of these physical quantities change. 12. K = 1 2 m dx dt 2 , U = 1 2 kx 2 . We can derive the expression for kinetic energy by first noting that the work done on a particle moving from x = x 1 to x = x 2 subject to a force F ( x ) is W = R x 2 x 1 dxF ( x ). Since F ( x ) = m dv dt , W = m R x 2 x 1 dx dv dt = W = m R v 2 v 1 vdv = 1 2 m ( v 2 2- v 1 2 ). If we define K = 1 2 mv 2 , W = K 2- K 2 , which is the work-energy theorem....
View Full Document

This note was uploaded on 04/29/2008 for the course PHYS 6B taught by Professor Wu during the Winter '08 term at UCLA.

Page1 / 16

mt1_sample_solution - Sample Exam 1 Solutions Antoine...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online